2011
DOI: 10.5251/ajsir.2011.2.3.391.400
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic and in vitro antioxidant activity of ethanolic extracts of Ficus racemosa Linn. fruits

Abstract: The present study was carried out to evaluate hypoglycemic and in vitro antioxidant activity of ethanolic extracts of Ficus racemosa Linn. Fruits (EEFR). Antidiabetic potential of the plant extracts was evaluated by oral administration at the doses of 100 and 200 mg/kg on alloxan induced Swiss albino mice and in vitro antioxidant potential was investigated by using 1, 1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging activity and total antioxidant capacity. Glucose tolerance test reveals that the extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
0
12
1
Order By: Relevance
“…Examples of such studies are: Akter, Mahabub-Uz-Zaman, and Rahman, 2013; Al-Amin, Uddin, Rizwan, and Islam, 2013; Ali et al, 1993; Amran, Sultan, Rahman, and Rashid, 2013; Bhuyan, Rokeya, Masum, Hossain, and Mahmud, 2010; Borhanuddin, Shamsuzzoha, and Hussain, 1994b; A. Chowdhury and Biswas, 2012; A. R. Das, Mostofa, Hoque, Das, and Sarkar, 2010; Habib and Gafur, 2003; J. M. A. Hannan et al, 2003; E. Haque, Saha, Islam, and Islam, 2012; M. A. Hossain et al, 2012; Md Alamgir Hossain, Roy, Ahmed, Chowdhury, and Rashid, 2007b; M. Z. Hossain, Shibib, and Rahman, 1992; Islam et al, 2009; M. A. Islam et al, 2011; I. A. Jahan et al, 2009; Mostofa et al, 2007b; Mowl, Alauddin, Rahman, and Ahmed, 2009; Rafiq, Sherajee, Nishiyama, Sufiun, and Mostofa, 2009; Md Masudur Rahman, Hossain, Siddique, Biplab, and Uddin, 2012b; Md Mahfuzur Rahman, Sayeed, Haque, Hassan, and Islam, 2012; M. W. Rahman et al, 2005; Rokeya, Bhowmik, Khan, and Khter, 2009; M. G. Roy et al, 2010; Shahreen et al, 2012; Shibib, Khan, and Rahman, 1993; Sikder, Kaisar, Rahman, Hussain, and Rashid, 2011; Talukder, Khan, Uddin, Jahan, and Alam, 2012; Urmi et al, 2012; Zulfiker et al, 2011 [ 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 ]. These scientific studies emphasized the correlation among traditional use and the pharmacological properties of antidiabetic plants.…”
Section: Phytochemical and Experimental Studies Of Antidiabetic Plants In Bangladeshmentioning
confidence: 99%
“…Examples of such studies are: Akter, Mahabub-Uz-Zaman, and Rahman, 2013; Al-Amin, Uddin, Rizwan, and Islam, 2013; Ali et al, 1993; Amran, Sultan, Rahman, and Rashid, 2013; Bhuyan, Rokeya, Masum, Hossain, and Mahmud, 2010; Borhanuddin, Shamsuzzoha, and Hussain, 1994b; A. Chowdhury and Biswas, 2012; A. R. Das, Mostofa, Hoque, Das, and Sarkar, 2010; Habib and Gafur, 2003; J. M. A. Hannan et al, 2003; E. Haque, Saha, Islam, and Islam, 2012; M. A. Hossain et al, 2012; Md Alamgir Hossain, Roy, Ahmed, Chowdhury, and Rashid, 2007b; M. Z. Hossain, Shibib, and Rahman, 1992; Islam et al, 2009; M. A. Islam et al, 2011; I. A. Jahan et al, 2009; Mostofa et al, 2007b; Mowl, Alauddin, Rahman, and Ahmed, 2009; Rafiq, Sherajee, Nishiyama, Sufiun, and Mostofa, 2009; Md Masudur Rahman, Hossain, Siddique, Biplab, and Uddin, 2012b; Md Mahfuzur Rahman, Sayeed, Haque, Hassan, and Islam, 2012; M. W. Rahman et al, 2005; Rokeya, Bhowmik, Khan, and Khter, 2009; M. G. Roy et al, 2010; Shahreen et al, 2012; Shibib, Khan, and Rahman, 1993; Sikder, Kaisar, Rahman, Hussain, and Rashid, 2011; Talukder, Khan, Uddin, Jahan, and Alam, 2012; Urmi et al, 2012; Zulfiker et al, 2011 [ 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 ]. These scientific studies emphasized the correlation among traditional use and the pharmacological properties of antidiabetic plants.…”
Section: Phytochemical and Experimental Studies Of Antidiabetic Plants In Bangladeshmentioning
confidence: 99%
“…Superoxide anions are well known to damage biomolecules either directly or indirectly by producing -OH, H2O2, singlet oxygen, or peroxynitrite during aging and pathological conditions like ischemic reperfusion injury. It has also been observed that superoxides directly involve lipid peroxidation [36,37]. The antioxidant potential of RCE and WSE was assessed.…”
Section: Superoxide Anion Scavenging Activity Of Extractsmentioning
confidence: 99%
“…Among the herbs, Syzygium cumini seeds and Ficus racemosa fruits have many common antidiabetic phytochemicals. They are also renowned for their hepatoprotective and hypolipidemic role (Zulfiker et al, 2011;Behera et al, 2014). The previous researchers use either S. cumini seeds or F. racemosa fruits in individual dose.…”
Section: Introductionmentioning
confidence: 99%